2001
DOI: 10.1080/10641190152481412
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Acoustic Backscatter Due to High Abundance of Sand Dollars, Dendraster excentricus

Abstract: Detailed acoustic surveys of benthic sediments were conducted in July 1995 and September 1998 in the vicinity of Humboldt Bay, California. During these surveys, a band of enhanced acoustic backscatter was observed oVshore from the bay entrance, approximately parallel to the isobaths, in water depths ranging from 16± 24 m. In order to assess the cause of the increase in backscatter levels, a more comprehensive study was conducted in August and September 1999 using 100 kHz side-scan sonar, bottom grab sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…No synoptic observations were made of seabed surface roughness, but many studies have demonstrated the importance of roughness at this site (e.g. Cacchione et al, 1999;Fenstermacher et al, 2001;Ferrini and Flood, 2003). Backscatter intensity that we observe at this site ranges from À 32.5 to À 15 dB, and sediment type ranges from coarse sand to medium silt (median grain size: 0f to 5.5f).…”
Section: Roughness Predictionmentioning
confidence: 97%
See 1 more Smart Citation
“…No synoptic observations were made of seabed surface roughness, but many studies have demonstrated the importance of roughness at this site (e.g. Cacchione et al, 1999;Fenstermacher et al, 2001;Ferrini and Flood, 2003). Backscatter intensity that we observe at this site ranges from À 32.5 to À 15 dB, and sediment type ranges from coarse sand to medium silt (median grain size: 0f to 5.5f).…”
Section: Roughness Predictionmentioning
confidence: 97%
“…In addition to ripples, roughness in the form of shells (e.g. sand dollars; Fenstermacher et al, 2001) or biogenic structures (Urgeles et al, 2002) can result in increased backscatter intensity.…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, the detection of buried objects using acoustics is impeded by the high attenuation of acoustic waves due to scattering and absorption in the sediment [15,16]. Consequently, there are only a few examples of benthic surveys that identify details below broad habitat types using acoustics [32] and, to date, it has not been possible to reliably identify invertebrate species directly from acoustic data. A logical next step would be to incorporate how biological communities modify seafloor sediment in models of seafloor processes [7], but progress in this area has been slow due to a lack of detailed mechanistic information about specific organism–sediment interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Typically the differences between muddy and rocky seafloor are on the order of 10-20 dB . However, recent regional studies have revealed that backscatter intensity may be influenced by other factors such as the occurrence of benthic fauna (Fenstermacher et al, 2001;Edwards et al, 2003;Kostylev et al, 2003;Valentine et al, A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 3 2003), sediment compaction (Nitsche et al, 2004), the rate of the sediment reworking by organisms (Borgeld et al, 1999;Urgeles et al, 2002), the presence of anthropogenic organic residues (Lewis et al, 2000), the content of natural hydrocarbons in fluidventing structures such as mud volcanoes (Fonseca et al, 2002;Sager et al, 2003;Somoza et al, 2003) or the presence of authigenic carbonates related to the bacterial oxidation of methane (Orange et al, 2002;Díaz-del-Río et al, 2003).…”
Section: Introductionmentioning
confidence: 99%